1984
DOI: 10.1093/nar/12.11.4493
|View full text |Cite
|
Sign up to set email alerts
|

The complete nucleotide sequence of a legumin gene from pea (Pisum sativumL.)

Abstract: One of several genes coding for the major pea storage protein, legumin, has been completely sequenced. The sequence covers the whole of the transcribed region, plus 5' and 3' untranscribed sequences. The predicted protein sequence starts with a signal peptide and is followed by the legumin alpha polypeptide sequence of 36. 44kd and the beta polypeptide sequence of 20. 19kd . Compared to other legume storage proteins, the alpha and beta polypeptide sequences encoded by this legumin gene, which contain 3 met and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(95 citation statements)
references
References 50 publications
4
91
0
Order By: Relevance
“…Rice glutelin shares several characters in common with leguminous 11 S globulin. When the deduced amino acid sequence of the glutelin precursor was compared with those of pea legumin [5] and soybean glycinin [a], it showed 38 and 37% homology to them. The sequence of the acidic subunit is less conserved than that of the basic subunit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice glutelin shares several characters in common with leguminous 11 S globulin. When the deduced amino acid sequence of the glutelin precursor was compared with those of pea legumin [5] and soybean glycinin [a], it showed 38 and 37% homology to them. The sequence of the acidic subunit is less conserved than that of the basic subunit.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the nucleotide sequence of glutelin cDNA was determined, from which the complete amino acid sequence of the glutelin precursor was deduced. When compared with the amino acid sequences of pea legumin [5] and soybean glycinin [6], we found that rice glutelin shows homology to these leguminous 11 S globulins. This is the first complete nucleotide sequence of the rice storage protein gene.…”
Section: Introductionmentioning
confidence: 99%
“…In these alternating patterns, the sequence spanning residues 244-254 of the A2Bra subunit precursor shows a relatively striking hydrophilicity, suggesting that it may be localized near the surface of the protein molecule. Although these hydrophilic sequences contained repeated units in glycinin A3B4 [S] and legumin cup [9,18], there are none in the A2Bra subunit precursor. However, these hydrophilic regions which are located immediately upstream of the post-translational cleavage sites of glycinin and legumin precursors appear to be functionally similar.…”
Section: The Predicted Protein Sequencesmentioning
confidence: 99%
“…Rice glutelins share amino acid sequence homology with the 11S globulins of legume species, such as soybean glycinin [1] and pea legumin [2], but differ from other globulins in their insolubility in saline solutions. The glutelins are synthesized as preproglutelin (ca.…”
Section: Introductionmentioning
confidence: 99%